2021
DOI: 10.31234/osf.io/56kdv
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Metamemory for Prospective Memory Performance in Younger and Older Adults: Does the Reference Point Affect our Judgments?

Abstract: The present study investigated age differences in the ability to predict prospective memory (PM) performance. A sample of younger (N = 88) and older (N = 88) participants completed an event-based PM task embedded in an ongoing task. Metamemory was measured by asking participants to predict their performance before completing the PM task and complete some questionnaires on self-perceptions of everyday memory ability. We manipulated A) the reference point used to evaluate performance and B) the order of presenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 37 publications
0
1
1
Order By: Relevance
“…In contrast with the evidence above suggesting that older adults may be more overconfident about their memory ability than younger adults, in a recent study, Scarampi and Kliegel (2021) found that both age groups were similarly underconfident when asked to predict their performance at a prospective memory task. Still, other studies have shown that confidence in one's memory ability tends to decline with age (Dobbs & Rule, 1987).…”
Section: Aging and Metacognitive Monitoringcontrasting
confidence: 65%
“…In contrast with the evidence above suggesting that older adults may be more overconfident about their memory ability than younger adults, in a recent study, Scarampi and Kliegel (2021) found that both age groups were similarly underconfident when asked to predict their performance at a prospective memory task. Still, other studies have shown that confidence in one's memory ability tends to decline with age (Dobbs & Rule, 1987).…”
Section: Aging and Metacognitive Monitoringcontrasting
confidence: 65%
“…In contrast with the evidence above suggesting that older adults may be more overconfident about their memory ability than younger adults, in a recent study, Scarampi and Kliegel (2021) found that both age groups were similarly underconfident when asked to predict their performance at a prospective memory task (Scarampi & Kliegel, 2021). Still, other studies have shown that confidence in one's memory ability tends to decline with age (Dobbs & Rule, 1987).…”
Section: Ageing and Metacognitive Monitoringmentioning
confidence: 76%